A Subdivision Based Iterative Collocation Algorithm for Nonlinear Third-Order Boundary Value Problems - Syeda Tehmina Ejaz; Ghulam Mustafa (Advances in Mathematical Physics)
We construct an algorithm for the numerical solution of nonlinear third-order boundary value problems. This algorithm is based on eight-point binary subdivision scheme. Proposed algorithm is stable and convergent and gives more accurate results than fourth-degree B-spline algorithm.